Wilsonian flows and background fields - Litim, Daniel F.; Pawlowski, Jan M. (Physics letters, 2002)
We study exact renormalization group flows for background field dependent regularizations. It is shown that proper-time flows are approximations to exact background field flows for a specific class of regulators. We clarify the rôle of the implicit scale dependence introduced by the background field. Its impact on the flow is evaluated numerically for scalar theories at criticality for different approximations and regularizations. Implications for gauge theories are discussed.